Associations Between Perceptions of School Connectedness and Adolescent Health Risk Behaviors in South African High School Learners. (23rd July 2013) - Govender, Kaymarlin; Naicker, Sara Naomi; Meyer‐Weitz, Anna; Fanner, Joanne; Naidoo, Avanya; Penfold, Wendy Leigh
ABSTRACT: BACKGROUND: This study investigated the relationship between school connectedness and health risk behaviors, specifically, substance abuse, violence‐related behaviors, sexual risk behaviors, and suicidal ideation among school‐going adolescents. School connectedness was understood to encompass a range of aspects pertaining to a learner's sense of belonging to the school. We hypothesized that strong perceptions of school connectedness will more likely be associated with lower levels of risk behaviors among school‐going adolescents. METHODS: The study was conducted in 2 neighboring public co‐educational schools in Durban, South Africa. Independent measures assessed school connectedness, substance abuse, violence‐related behaviors, sexual risk behaviors, and suicidal ideation. RESULTS: Strong negative correlations were found between adolescents' perceptions of school connectedness and the 4 health risk behaviors, particularly suicidal ideation. The relative importance of risk factors was also evidenced in the sample. CONCLUSIONS: Adolescents with lower perceptions of school connectedness were more likely to engage in various risk behaviors, supporting the literature that a lack of school connectedness can act as a risk factor for adolescent involvement in clustering of risk behaviors. Further the relative weighting of individual risk factors, it is argued, was an effect of the sociocultural context of the study.